Congenital self-healing reticulohistiocytosis: a case report - Shricharith Shetty; Vidya Monappa; Kanthilatha Pai; Raghavendra Rao; Sathish Pai (Our Dermatology Online, 2014)
Congenital self-healing reticulohistiocytosis (CSHRH) is a benign type of Langerhans cell histiocytosis (LCH) also known as Hashimoto-Pritzker disease. Clinically it presents with skin lesions at birth or in neonatal period, usually without any systemic involvement. Lesions often heal spontaneously in period of weeks to months. We report a case of CSHRH presenting with skin lesions at birth, describing need to make an early diagnosis and to have a multidisciplinary approach with regular follow-up, in managing this rare type of LCH.